2007
DOI: 10.1074/jbc.m702333200
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Bonds between Nitrogen Donors and the Semiquinone in the Qi-site of the bc1 Complex

Abstract: The ubisemiquinone stabilized at the Q i -site of the bc 1 complex of Rhodobacter sphaeroides forms a hydrogen bond with a nitrogen from the local protein environment, tentatively identified as ring N from His-217. The interactions of 14 N and 15 N have been studied by X-band (ϳ9.7 GHz) and S-band (3.4 GHz) pulsed EPR spectroscopy. The application of S-band spectroscopy has allowed us to determine the complete nuclear quadrupole tensor of the 14 N involved in H-bond formation and to assign it unambiguously to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 63 publications
5
48
1
Order By: Relevance
“…(40). On the other hand, this coupling constant is larger than the K values reported for either the deprotonated or protonated nitrogens of the imidazole residue (36). That rules out histidine as a hydrogen bond partner to the SQ of cyt aa 3 -600.…”
Section: Table 1 Hyperfine Tensors Of the Protons H1-h4 (Mhz) Derivedmentioning
confidence: 67%
See 1 more Smart Citation
“…(40). On the other hand, this coupling constant is larger than the K values reported for either the deprotonated or protonated nitrogens of the imidazole residue (36). That rules out histidine as a hydrogen bond partner to the SQ of cyt aa 3 -600.…”
Section: Table 1 Hyperfine Tensors Of the Protons H1-h4 (Mhz) Derivedmentioning
confidence: 67%
“…This is due to the influence of the nuclear quadrupole interaction (3,4,6,36 (3,36), suggesting that more than one nitrogen interacts with the SQ, accompanied by the transfer of unpaired spin density onto their nuclei.…”
Section: Resultsmentioning
confidence: 99%
“…This scheme is supported by the observation that USQ i is in anionic form (USQ i Ϫ ) (76,143). Crystal structures revealed two regions rich in protonable groups of amino acid side chains and water molecule paths for consideration as proton paths linking the catalytic site with the membrane surface (129,153).…”
Section: B Quinone Binding Q I Sitementioning
confidence: 79%
“…Mutagenic studies and EPR spectroscopy identified conservative residues responsible for binding and stabilization of quinone and USQ i (76,112,120,143 (149,242).…”
Section: B Quinone Binding Q I Sitementioning
confidence: 99%
“…More recently similar experiments have been performed on the bacterial bc 1 complex from Rhodobacter (Rb.) sphaeroides and a direct binding to histidine has been proposed [23,24]. When applying EPR spectroscopy to study electron-transfer intermediates in mitochondrial or bacterial respiratory chains, it is important to realize that presence of several paramagnetic species is a common occurrence.…”
Section: Introductionmentioning
confidence: 99%